Mercury at environmental relevant levels affects spermatozoa function and fertility capacity in bovine sperm. Issue 4 (16th February 2019) - Silva, Elane Fabíola de Sousa Jerônimo da; Missio, Daniele; Martinez, Caroline Silveira; Vassallo, Dalton Valentim; Peçanha, Franck Maciel; Leivas, Fabio Gallas; Brum, Daniela dos Santos; Wiggers, Giulia Alessandra
ABSTRACT: Over the last several years human sperm quality was found to be significantly reduced and the role environmental contaminants play in this phenomenon remain to be determined. Mercury (Hg) is one of the most widespread contaminants; however the correlation between metal exposure and adverse consequences on human and animals fertility are not completely established. The aim of this study was to determine the effects of direct exposure to inorganic Hg on male gametes using spermatozoa (bovine sperm) which characteristically resemble human sperm. Sperm were divided and incubated for 0.5, 1 or 2 h at low levels of Hg: i) Control: without exposure; ii) Hg8 nM: mercury chloride (HgCl2 ) at 8 nM and iii) Hg8 μM: HgCl2 at 8 μM. Sperm kinetics, morphology, sperm membrane integrity, and in vitro fertilization were assessed. In addition the levels of reactive oxygen species (ROS), lipid peroxidation and total antioxidant capacity were measured. Hg exposure for 2 h impaired sperm morphology and membrane integrity as well as kinetic parameters including curvilinear velocity and straight-line velocity, which are needed for fertilization as evidenced by the reduced fertilization rate in 8 μM Hg-treated gametes. Hg enhanced oxidative stress in male sperm as reflected by elevated levels of ROS and lipid peroxidation and decreased antioxidant capacity. Data demonstrated that low levels of Hg when incubated with spermatozoa are sufficient to increase oxidative stress, adversely affect sperm quality parameters, subsequently impairing sperm fertility capacity.